KINETICS OF PLATELET COUNT IN P. VIVAX MALARIA; A STUDY IN YOUNG SOLDIERS - Tariq Bashir Tareen; Zahid Farooq Baig; Karamat Hussain Bokhari; Grana Khattak (Pakistan Armed Forces Medical Journal, 2020)
Objective: To estimate the time of recovery from moderate to severe thrombocytopenia in young soldiers with P. vivax malaria.